Evaluation of heating process for the rectangular mold cavity by external gas-assisted heating - Phạm Sơn Minh; Đỗ Thành Trung; Nguyễn Hộ; Phan Thế Nhân (Journal of Technical Education Science, 2015)
For enhancing surface temperature of the rectangular mold cavity before injecting melt plastic into the mold, a gas assisted mold heating method (GAMH) was applied. In this research, a 200oC air flow source was used for heating the rectangular mold cavity with the heating area size of 175mm x 12mm. Based on the simulated results with ANSYS CFX, it was clear that the GAMH had a good temperature distribution on the cavity surface of mold. Also, the simulated method showed the ability to predict quite accurately the temperature value on the cavity surface of mold. In addition, experiments were conducted to examine the temperature on the surface temperature as a function of heating time. The experimental results showed that the mold surface temperature increased rapidly in the first 10s, slowly in the next 20s, and became stable after that. At the stable state, the temperature values of several considered points of the mold varied from 83.5oC to 95oC.